Conversores compostos para o interlink entre os barramentos de baixa e extrabaixa tensão de nanorredes CC - Faistel, Tiago Miguel Klein (2022)
This thesis presents a study on isolated DC-DC converters for the interface between a low voltage bus, EBT (48 V), and a low voltage bus, BT (380 V) for a 1.2 kW residential DC-DC nanogrid. The proposed converter makes use of a composite structure where a DCX converter is designed to operate with a constant duty cycle at the point of minor losses. A DC regulator (DCR) controls the regulator for the extra-low voltage (EBT) DC bus that is regulated by the compound converter. In this sense, two performance indices were used to choose the DCX converter: the Effort Factor (Component Stress Factor - CSF) and Fryze Power Factor. CSF is an analytical method used to evaluate and compare converter topologies for a specific application. The Fryze power factor is a simple method for evaluating the amount of non-active power that is processed by a given circuit. The regulator is modeled and a compensator is designed to control the current through a reference provided by a droop loop. To reduce the non-active power processed by the DC regulator, an adjustable transformer was implemented to reduce the non-active power. The efficiency of the composite converter is compared with that of a cascade regulator. To validate the approaches, a 1.2 kW composite converter was designed, built and evaluated under different tests regarding static gain, waveforms, control and efficiency.